Report of meeting Researches in Didactics of Mathematics and Computer Sciences: January 21 – January 23, 2010, Debrecen, Hungary (Teaching Mathematics and Computer Science, 2010)
The meeting Researches in Didactics of Mathematics and Computer Sciences was held in Debrecen, Hungary from January 21 to January 23, 2010. The 42 Hungarian participants – including 16 PhD students – came from 5 countries, 14 cities and represented 25 institutions of higher education. The abstracts of the talks and the posters and also the list of participants are presented in this report.